Deep-coverage whole genome sequences and blood lipids among 16,324 individuals - Pradeep Natarajan (Nature Portfolio, 2018)
Common genetic variants associated with plasma lipids have been extensively studied for a better understanding of common diseases. Here, the authors use whole-genome sequencing of 16,324 individuals to analyze rare variant associations and to determine their monogenic and polygenic contribution to lipid traits.